Psoas:lumbar vertebra index: central sarcopenia independently predicts morbidity in elderly trauma patients - Ebbeling, L. (Eur J Trauma Emerg Surg, 2013)
INTRODUCTION: Central sarcopenia as a surrogate for frailty has recently been studied as a predictor of outcome in elderly medical patients, but less is known about how this metric relates to outcomes after trauma. We hypothesized that psoas:lumbar vertebral index (PLVI), a measure of central sarcopenia, is associated with increased morbidity and mortality in elderly trauma patients. METHODS: A query of our institutional trauma registry from 2005 to 2010 was performed. Data was collected prospectively for the Pennsylvania Trauma Outcomes Study (PTOS). Inclusion criteria: age >55 years, ISS >15, and ICU LOS >48 h. Using admission CT scans, psoas:vertebral index was computed as the ratio between the mean cross-sectional areas of the psoas muscles and the L4 vertebral body at the level of the L4 pedicles. The 50th percentile of the psoas:L4 vertebral index value was determined, and patients were grouped into high (>0.84) and low (≤0.83) categories based on their relation to the cohort median. Primary endpoints were mortality and morbidity (as a combined endpoint for PTOS-defined complications). Univariate logistic regression was used to test the association between patient factors and mortality. Factors found to be associated with mortality at p < 0.1 were entered into a multivariable model. RESULTS: A total of 180 patients met the study criteria. Median age was 74 years (IQR 63–82), median ISS was 24 (IQR 18–29). Patients were 58 % male and 66 % Caucasian. Mean PLVI was 0.86 (SD 0.25) and was higher in male patients than female patients (0.91 ± 0.26 vs. 0.77 ± 0.21, p < 0.001). PLVI was not associated with mortality in univariate or multivariable modeling. After controlling for comorbidities, ISS, and admission SBP, low PLVI was found to be strongly associated with morbidity (OR 4.91, 95 % CI 2.28–10.60). CONCLUSIONS: Psoas:lumbar vertebral index is independently and negatively associated with posttraumatic morbidity but not mortality in elderly, severely injured trauma patients. PLVI can be calculated quickly and easily and may help identify patients at increased risk of complications.